SUMO1 Modification Facilitates Avibirnavirus Replication by Stabilizing Polymerase VP1 - Wu, Huansheng (J Virol, 2019)
SUMOylation is a posttranslational modification that has crucial roles in diverse cellular biological pathways and in various viral life cycles. In this study, we found that the VP1 protein, the RNA-dependent RNA polymerase of avibirnavirus infectious bursal disease virus (IBDV), regulates virus replication by SUMOylation during infection. Our data demonstrated that the polymerase VP1 is efficiently modified by small ubiquitin-like modifier 1 (SUMO1) in avibirnavirus-infected cell lines. Mutation analysis showed that residues (404)I and (406)I within SUMO interaction motif 3 of VP1 constitute the critical site for SUMO1 modification. Protein stability assays showed that SUMO1 modification enhanced significantly the stability of polymerase VP1 by inhibiting K48-linked ubiquitination. A reverse genetic approach showed that only IBDV with I(404)C/T and I(406)C/F mutations of VP1 could be rescued successfully with decreased replication ability. Our data demonstrated that SUMO1 modification is essential to sustain the stability of polymerase VP1 during IBDV replication and provides a potential target for designing antiviral drugs targeting IBDV. IMPORTANCE SUMOylation is an extensively discussed posttranslational modification in diverse cellular biological pathways. However, there is limited understanding about SUMOylation of viral proteins of IBDV during infection. In the present study, we revealed a SUMO1 modification of VP1 protein, the RNA-dependent RNA polymerase of avibirnavirus infectious bursal disease virus (IBDV). The required site of VP1 SUMOylation comprised residues (404)I and (406)I of SUMO interaction motif 3, which was essential for maintaining its stability by inhibiting K48-linked ubiquitination. We also showed that IBDV with SUMOylation-deficient VP1 had decreased replication ability. These data demonstrated that the SUMOylation of IBDV VP1 played an important role in maintaining IBDV replication.